Antibacterial Activity of The Secondary Metabolites Produced by Endophytic Fungi Isolated from Acanthus ilicifolius Plant - Gusti Ayu Widayanti; Hary Widjajanti; Salni Salni (Indonesian Journal of Environmental Management and Sustainability, 2019)
Twelve endophytic fungi were isolated from the Acanthus ilicifolius plant. Two of them have the best antibacterial activity, namely Culvularia lunata and Diaporthe phaseolorum. Fungi can produce secondary metabolites that have the potential as antibacterial compounds. This study aims to isolate antibacterial compounds using column chromatography methods and test the antibacterial activity using diffusion methods to use paper discs. Isolation of secondary metabolites produces 27 eluates. From TLC, it is known that the endophytic fungi Culvularia lunata produce an active compound as an antibacterial that is phenol compound. Endophytic fungi Diaporthe phaseolorum produces three types of active compounds as antibacterial namely phenol, terpenoids, and alkaloids, each component of the active compound are tested for sensitivity to bacterias Escherichia coli, Staphylococcus aureus, Shigella dysenteriae, and Salmonella typhi. MIC values ??of terpenoid compounds with concentrations of 125-250 ppm are antibacterial compounds with good activity against Escherichia coli, Staphylococcus aureus, Shigella dysenteriae, and Salmonella typhi.